Optimalisasi Prestasi Akademis Berbasis Hipnosis - Dewi Puspaningtyas Faeni; Ratih Puspitaningtyas Faeni; Retno Fuji Oktaviani; Ravindra Safitra Hidayat; Rinny Meidiyustiani; Dendi Anggi Gumilang (Penerbit Goodwood, 2021)
Purpose: Optimization of academic achievement based on Hypno-education aims to improve achievement using the hypnosis method, namely the subconscious power method. This methodology uses the power of suggestion to the theta waves in the student's subconscious mind. The achiever personality is inserted into the theta wave. The population of participants is students majoring in Management in Good Corporate Governance at the IPMI International Business School Campus of 72 schools. Students sit quietly in the lecture chair starting with fun things such as eye exercises, brain exercises, motoric movements and then calm with the aim of ice breaking, so that the atmosphere is conducive and not tense. Conducive conditions that are not tense will lead to a pleasant atmosphere so that the brain is open to being flexible when good suggestions are inserted. When the students are bowed down in a sleepy condition or half asleep and half awake, the next story is stimulated by theta music. This condition is the condition of the students' brains very ready for positive suggestions. The main objective is for students who are active in studying, do not receive lessons, and continuously return to the study table to pay more attention to their lessons. Method: This Community Service is the 10th time this activity has collected data on student achievement results before and after therapy. The data tabulation of the Mid-Semester Examination values (UTS) or Final Semester (UAS) before and after hypnosis therapy is an indica tor that believes in hypno-education. Results: The results of student achievement increased sharply in their academic achievement